First-Time Father’s Risk Factors of Paternal Perinatal Psychological Distress: A Scoping Review - Sadaf Zindani; Julie Chartrand; Jean Hannan; J. Craig Phillips (American Journal of Men's Health)
Fathers can experience psychological distress during the paternal perinatal period. The effects of paternal perinatal psychological distress (PPPD) are multileveled. Little research is available about PPPD in first-time fathers. The purpose of this review is to explore the literature on risk factors contributing to PPPD in first-time fathers. The Arksey & O’Malley framework was used to guide this scoping review. The Population, Concept, and Context (PCC) framework was used for answering the review question “What evidence is available about factors contributing to PPPD in first-time fathers?” Five databases (CINAHL, EMBASE, MEDLINE, PsycINFO, and PubMed) were used to retrieve relevant, full-text, English references from January 01, 2020, to January 04, 2023. A data extraction tool was developed to identify risk factors assessed in the included studies. The Socio-Ecological Model (SEM) was used for analyzing the extracted data according to the four socio-ecological levels, i.e., individual, relationship, community, and societal. A total of 18 references reporting on 16 studies were included in the review. Fifty-six tools were used for assessing the risk factors contributing to PPPD in first-time fathers. Limited understanding was established about risk factors because tools lacked gender sensitivity. Risk factors aligned with 12 domains (e.g., psychological, relationship, social, and physical). Most domains corresponded with the individual level of SEM. Only two domains corresponded with the societal level of SEM. The literature indicates there are few studies about PPPD experienced by first-time fathers. This scoping review adds to the literature on the mental health care gaps for this population. Further research on measuring PPPD may improve individual and family functioning during the perinatal period.